La pilule : biologisation de la contraception et régulation sociale - Claire Grino (Genre, Sexualité et Société)
Unlike previous contraceptive methods, hormonal contraception mobilizes vital processes of the body. But if we disagree with the idea that reproduction is a biological constraint imposed on women, how can we hope that the manipulation of physiology can help to resolve a social problem ? To ask this seemingly simple question amounts in fact to wondering whether the hormonal shaping of bodies can alter gender relations ; and in turns it points at the articulation of bodies, subjectivities and gender identities. Therefore this article examens how bodies are objectified through hormonal contraception. As this view on the constructedness of gendered and sexual bodies differs from the classical constructionist approach and its focus on behaviours (mainly in relation to medical mediation, time, consciousness and effort), the efficacy of the pill is attributed to the opposition between the two technologies of gender. In a second step the modality of feminist engagement will be confronted with these new biomedical ways of constructing gender.